Optimalisasi Kinerja Layanan Publik dalam Meningkatkan Kualitas Pelayanan: Studi pada Pelayanan Via Online (Plavon) Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sidoarjo - Bayu Purnomo; Auditya Desvananda Putra Purwanto; Intan Nuraini Rianto; Magda Faradiba Maulidia Agung (Universitas 17 Agustus 1945 Semarang, 2025)
This research was used to analyze the performance of public services, especially on the Plavon platform that’s provided by employees at the Sidoarjo Regency of Population and Civil Registration Service. The theory that researchers use takes from Robbins in (Aziz, 2022) which contains five indicators of Work Quality, Quantity, Timeliness, Effectiveness, and Independence. The type of researchers used for this research is descriptive qualitative methods with sources and types pf research data divided into primary data and secondary data through the process of taking activity documentation, employee interview, and observing activities which can then be used to draw conclusions. The findings in this research are in the for of information related to incoming complaints which convey that there are still errors in input made by employees on the Plavon Disdukcapil Sidoarjo platform which that will then be evaluated and given direction, Communication and coordinate are running well, the human resources are inversely proportional to demographic condition in Sidoarjo which results in the fulfillment of services using an overtime system, and then to the implementation of employee discipline supported by performance motivation in the reward & punishment categorization.